The presence of occipital hair in the pilonidal sinus cavity—a triple approach to proof - Doll, Dietrich; Bosche, F.; Hauser, A.; Moersdorf, P.; Sinicina, I.; Grunwald, J.; Reckel, F.; Luedi, M. M. (Springer, 2018)
Purpose: Hair in the pilonidal sinus is not growing within the sinus cavity, as hair follicles are not present there. Not few pilonidal patients do not have intergluteal hair, which is said to be the causative agent of folliculitis and pilonidal genesis. So, what is the real source of the hair forming the typical pilonidal hair nest? Methods: A trifold approach was used: First, axial hair strength testing of pilonidal hair and body hair harvested from head, lower back (glabella sacralis), and cranial third of intergluteal fold. Hair strength match was compared clinically. Second, comparative morphological examination by expert forensic biologist of hair from sinus and dorsal body hair. Third, statistical Bayesian classification of every single sinus hair based on its strength was done to determine the most probable region of origin. Results: Using clinical hair strength comparison, in 13/20 patients, head hair is the stiffest hair, followed by intergluteal hair. Only in 6/20 patients, this is the case with hair from the glabella sacralis. According to comparative morphological comparison, a minimum of 5 of 13 hair nests with possible hair allocation examined contain hair from the occiput. In 5/18 nests, hair could not be determined to a specific location though. Statistical classification with correction for multiple testing shows that 2 nests have hair samples that are at least 100 times more probable to originate from head or lower back than from intergluteal fold. Conclusion: We saw our null hypothesis that hair in the sinus cavity is from the intergluteal region^ rejected by each of three different approaches. There is strong evidence that occipital hair is present regularly in pilonidal sinus nests. We should start thinking of occipital hair as an important hair source for the development of the pilonidal hair nest.
Keywords: Hair; Pilonidal sinus; Scalp; Occiput; Cut hair; Electron microscopy; Pathogenesis; SDG-3: Good health and well-being